2006
DOI: 10.1007/s00268-005-0606-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients at Low Risk for Thyroidectomy‐Related Hypocalcemia by Intraoperative Quick PTH

Abstract: Quick PTH monitoring during total thyroidectomy is a useful means for identifying low-risk patients for postoperative hypoparathyroidism and candidates for early, safe discharge. Furthermore, it is an objective method complementary to the surgeon's judgement of the intraoperative function of parathyroid glands, which should be implanted in the event of a 75%-80% decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 21 publications
3
56
1
1
Order By: Relevance
“…Almost all studies define hypocalcemia as either low serum calcium or development of symptoms of hypocalcemia (9,11,(15)(16)(17)(18)(19)(21)(22)(23)(24)(25)(26). We used only the symptoms of hypocalcemia because we believe that mixing two parameters (biochemical hypocalcemia and symptomatic hypocalcemia) can introduce a bias.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies define hypocalcemia as either low serum calcium or development of symptoms of hypocalcemia (9,11,(15)(16)(17)(18)(19)(21)(22)(23)(24)(25)(26). We used only the symptoms of hypocalcemia because we believe that mixing two parameters (biochemical hypocalcemia and symptomatic hypocalcemia) can introduce a bias.…”
Section: Resultsmentioning
confidence: 99%
“…Lecerf et al (19) indicated that the PTH decline was more precise than the PTH level alone in early diagnosis of hypocalcemia. Other several studies also have reported that percentage decline of the perioperative PTH level in the immediate postoperative period was useful to predict hypocalcemia, using the thresholds of PTH decline from 50.0% to 75.7% (20)(21)(22)(23). We demonstrated that the percentage decline of preoperative PTH level, using the cutoff value 75.0%, showed significant difference in the chance of transient hypocalcemia (P<0.001).…”
Section: Discussionmentioning
confidence: 58%
“…10 Similar threshold value (75.7%) is obtained by Di Fabio et al in a study of 81 patients with thyroidectomy. 12 Analysis of their results takes into account the fact that the average decrease in PTH is more pronounced after thyroidectomy (53%) compared to cases with unilateral lobectomy (20%) which is consistent with the signifi cantly lower incidence of postoperative hypoparathyroidism after partial thyroid resections. 12 The abovementioned meta-analysis of Noordzij et al states that the a decrease in PTH by 65% compared to preoperative levels measured 1 to 6 hours after thyroidectomy has a 96.45% sensitivity and 91.4% specifi city for the development of hypocalcemia.…”
Section: Hypocalcaemiamentioning
confidence: 55%
“…12 Analysis of their results takes into account the fact that the average decrease in PTH is more pronounced after thyroidectomy (53%) compared to cases with unilateral lobectomy (20%) which is consistent with the signifi cantly lower incidence of postoperative hypoparathyroidism after partial thyroid resections. 12 The abovementioned meta-analysis of Noordzij et al states that the a decrease in PTH by 65% compared to preoperative levels measured 1 to 6 hours after thyroidectomy has a 96.45% sensitivity and 91.4% specifi city for the development of hypocalcemia. 9 The different threshold levels of PTH decline provided in individual studies are most likely related to differences in the methods of PTH measurement, accepted reference ranges of calcium and the design of studies.…”
Section: Hypocalcaemiamentioning
confidence: 55%